A Socio-Economic Pilot Study on Indian Peri-Urban Dairy Production - Nayantara Ghotge; András Gáspárdy (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2016)
While livestock rearing and dairy production on a subsistence level has been a traditional occupation in rural India, changes in policy and governance and production, both at a national and international level have had a profound effect on livestock rearing practices, production and farming systems, and the indigenous biodiversity of the country. Changes in the dairy sector in the last 50 years have had tremendous alterations, leading to a new type of surplus market oriented dairy production system. India now leads the world in global milk production,  although much of this is attributed to the high ruminant population and the yield per animal remains low. By analysing a small group of dairy farmers in a peri-urban region, it may begin to represent the structure of daily production in India with regards to the farmers themselves, the animals they keep, the management systems they practice and their potential for the future.